Transformation of the Banking Sector of Ukraine: Reasons and Consequences - Khutorna, Myroslava (Journal of Finance and Financial Law, 2017)
This paper is devoted to the consideration of the preconditions and results of the banking sector of Ukraine transforming, its influence on the sector’s productivity, stability and significance for the real economy. It’s grounded that banking sector of Ukraine has seriously weakened its potential for the economic development stimulation. On the one hand, due to the banking sector clearance from the bad and unscrupulous banks the system has become much more sensitive to the monetary instruments and its state is going to be more predictable and better controlled. But on the other hand, massive banks’ liquidations have caused the worsening of the confidence in financial system and radical increasing of the market concentration the highest degree of which is observed in the householders’ deposit market.